Analisis Prosedur Perawatan Mesin Motorizer Sedimen di PDAM Tirta Pakuan Kota Bogor - Rio Nurman Gumilar; M Tirtana Siregar (Jurnal Sistem dan Manajemen Industri, 2017)
This research have objective to determine the application of procedures, mismatches work processes and maintenance of machinery repair and analyze the causes of motor engine damage in the PDAM Tirta Pakuan Bogor City. The data used in this research are primary and secondary data. Primary data obtained through observations and interviews to the parties concerned in the mechanical and electrical parts. Secondary data in the form of data SOP maintenance and repair machine from company. Descriptive, comprative, and evaluative methods are used to analyze the actual condition and working procedures of maintenance and repair of machinery and to compare between the results obtained from this research on the implementation of the maintenance work process and the repair of machines there are still stages that are not executed according to the procedure. Using the Fishbone Diagram method, the most dominant type of damage occurring in the motorizer engine is a burning roll with a contribution rate of 53.125%. Using Pareto Diagram, this analysis can provide information for the company to pay more attention to the maintenance and repair activities of the machine so that the work process activities in the mechanical and electrical section run well and smoothly.